Vision of the victors: Brazil and the glorification of the war against Paraguay at the Nineteenth Century World's Fairs (2017)
Between 1862 and 1889, the Empire of Brazil participated in the most important World's Fairs in Europe and the United States. Especially within the scope of the exhibitions in Paris (1867), Vienna (1873), and Philadelphia (1876), one of the most frequently visualized topics was the Paraguayan War, which the exhibition organizers staged as an epical battle between 'civilization' and 'barbarism'. Besides, by constructing a 'national memory' of the victory over the descendants of the indigenous Guaraní, generally considered as 'savages', Brazil sought to present itself as regional power as well as a society whose racial composition was about to change by the process of 'whitening'.